Ulama Indunisiyya al-Qarni al-Thamin Ashr Tarjamah Muhammad Arshad al-Banjari wa Afkaruhu - Khairil Anwar (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1996)
In the 17th and 18th centuries, Haramayn be one of the intellectual centers of the most prominent Muslim in the Middle East. In these times of a number of Indonesian students studying in Haramayn participate. They are, when returning to Indonesia became the leading scholars, who later was instrumental in the development of Islam in the region. Among the scholars was Muhammad al-Banjari Arsyad. Career al-Banjari is one example of the dynamics of Islamic intellectualism in Indonesia. And, no doubt he has a big role in strengthening the rise of Sunni orthodoxy, in particular through fiqhnya very famous book, Sabil al-Muhtadin. This book is still used to this day among the Indonesian Muslim community.DOI: 10.15408/sdi.v3i4.794